2005
DOI: 10.1007/s11199-005-1298-0
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Children?s Personal Attributes Questionnaire (Short Form) with a Sample of African American Adolescents

Abstract: This article is based on a partial replication of a previous study in which the Children's Personal Attributes Questionnaire (CPAQ) was administered to a European American sample of children. The sample of the current study included 328 African American adolescents who completed the CPAQ's short form. Psychometric analysis indicated acceptable reliabilities on two of the three subscales, and gender differences were found. A factor analysis yielded three factors, each of which represented a combination of items… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 19 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…In our study, Cronbach's alphas were .68 for the CPAQ‐F and .59 for the CPAQ‐M, indicating low internal consistency. However, these values were similar to those observed in previous studies (Brody, Hay, & Vandewater, ; Hall & Halberstadt, ; Thomson & Zand, ). The detailed instructions for this scale in English and validity parameters considered as satisfactory are summarized by Hall and Halberstadt () and Thomson and Zand ().…”
Section: Methodssupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, Cronbach's alphas were .68 for the CPAQ‐F and .59 for the CPAQ‐M, indicating low internal consistency. However, these values were similar to those observed in previous studies (Brody, Hay, & Vandewater, ; Hall & Halberstadt, ; Thomson & Zand, ). The detailed instructions for this scale in English and validity parameters considered as satisfactory are summarized by Hall and Halberstadt () and Thomson and Zand ().…”
Section: Methodssupporting
confidence: 92%
“…Learning experiences following somatic symptoms and parents’ AS explained a proportion of the variance in children's AS, but children's EI and feminine/expressive traits are factors that may moderate the association between parental factors and children's AS. For the various scales, means are comparable to those observed in other studies for a non‐clinical population (Bouvard et al ., ; Mavroveli et al ., ; Muris et al ., ; Stassart & Etienne, ; Thomson & Zand, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…McGhee et al confirmed the validity of the SRES (BB and KK forms) by comparing scores derived from a sample of African Americans to the norming sample. A similar methodological approach was employed in Thomson and Zand's (2005) assessment of the CPAQ and Norwalk et al's (2011) review of the GRCS. Distinctly, Berkel (2004) demonstrated the validity of the SRES-KK by comparing the scale's psychometric properties between samples of African Americans and European Americans.…”
Section: Types Of Research Methodsmentioning
confidence: 99%